Relationship Between Nutrition Education and Dietary Compliance in Patients with Non-Communicable Diseases: A Cross-Sectional Study - Abubakar Betan; Anwarul Azim Majumder (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide, and dietary management is a cornerstone of their prevention and control. However, dietary compliance among patients with NCDs remains suboptimal. Nutrition education is considered a key strategy to improve adherence, yet evidence regarding its real-world association with dietary compliance across diverse NCD populations remains limited. This study aimed to analyze the relationship between nutrition education and dietary compliance among patients with non-communicable diseases. Methods: An analytical cross-sectional study was conducted among 100 adult patients diagnosed with hypertension, type 2 diabetes mellitus, dyslipidemia, or cardiovascular disease. Data were collected through structured interviews and medical record review. Nutrition education exposure was categorized as adequate or inadequate based on documented counseling sessions. Dietary compliance was assessed using a validated adherence questionnaire. Bivariate analysis was performed using the Chi-square test, and multivariate logistic regression was applied to determine independent associations, with statistical significance set at p<0.05. Results: 60% of respondents received adequate nutrition education, and 65% were dietarily compliant. Patients who received adequate nutrition education were significantly more likely to adhere to recommended dietary guidelines (p=0.001). After adjustment for sociodemographic and clinical variables, adequate nutrition education remained an independent predictor of dietary compliance (AOR=4.32; 95% CI: 1.85–10.09). Conclusion: Nutrition education is significantly associated with improved dietary compliance among patients with NCDs. Integrating structured and repeated nutrition education into chronic disease management programs may enhance adherence and improve long-term health outcomes